2014
DOI: 10.1155/2014/486521
|View full text |Cite
|
Sign up to set email alerts
|

Dementia Care: Intersecting Informal Family Care and Formal Care Systems

Abstract: Dementia is one of the major causes of disability and dependence amongst older people and previous research has highlighted how the well-being of people with dementia is inherently connected to the quality of their relationships with their informal carers. In turn, these carers can experience significant levels of emotional stress and physical burden from the demands of caring for a family member with dementia, yet their uptake of formal services tends to be lower than in other conditions related to ageing. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(68 citation statements)
references
References 19 publications
1
66
0
1
Order By: Relevance
“…Amidst growing recognition of caregiver needs (e.g., Sinha et al, 2016), our study elucidates a temporal dimension of how adult children may become increasingly vulnerable insofar as financial insecurity due to unforeseen care costs and care demands that threaten their employment, and political disenfranchisement when they lack the wherewithal (e.g., time, knowledge, language, social status) to access formal care services, or when utilizing services threatens their held values. Mistrust in and limited utilization of public home care and institutional care also adds to previous evidence (Singh et al, 2014; Ward-Griffin et al, 2012) that has called for systemic reforms that build trust with informal care partners by responding to their values and priorities (e.g., greater social opportunities and connectedness for PwDs, family care collaboration, financial security). Future work to drive such change may longitudinally examine care journeys and relationships, and the personal, social, and financial impacts to care partners once they are no longer caring for their parents.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Amidst growing recognition of caregiver needs (e.g., Sinha et al, 2016), our study elucidates a temporal dimension of how adult children may become increasingly vulnerable insofar as financial insecurity due to unforeseen care costs and care demands that threaten their employment, and political disenfranchisement when they lack the wherewithal (e.g., time, knowledge, language, social status) to access formal care services, or when utilizing services threatens their held values. Mistrust in and limited utilization of public home care and institutional care also adds to previous evidence (Singh et al, 2014; Ward-Griffin et al, 2012) that has called for systemic reforms that build trust with informal care partners by responding to their values and priorities (e.g., greater social opportunities and connectedness for PwDs, family care collaboration, financial security). Future work to drive such change may longitudinally examine care journeys and relationships, and the personal, social, and financial impacts to care partners once they are no longer caring for their parents.…”
Section: Discussionmentioning
confidence: 86%
“…Where prevailing notions assume that caregiver stress and burden are the results of providing PwDs with functional assistance (critiqued by Roth et al, 2015) and managing PwDs’ “behaviours” (critiqued by Dupuis, Wiersma, & Loiselle, 2012b), our study asserts an alternative explanation that stresses the consequences of limited family support and inadequate home and institutional care supports. Others have similarly charged the dominant construction of burden as imprecisely understanding the sources of stress (Roth et al, 2015) and burden (Bastawrous, 2013), and neglecting important structural factors that produce negative consequences for family care partners (Lilly et al, 2011; Singh et al, 2014; Ward-Griffin et al, 2012). While the mismatched logics between informal and formal care systems (Singh et al, 2014) and diminishing formal care support (Ward-Griffin et al, 2012) have been documented, our study adds two novel insights.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most non-randomized and quantitative descriptive studies (surveys) reported adequate sampling strategies and measurements. [52][53][54]56,[64][65][66]73,80,85,[87][88][89] Need for early diagnosis (to understand the behavioral problems and gain timely access to resources). …”
mentioning
confidence: 99%